For a just and better world : engendering anarchism in the Mexican borderlands, 1900-1938 - Hernández, Sonia, 1976- (University of Illinois Press, 2021)
"Caritina Piña Montalvo personified the vital role played by Mexican women in the anarcho-syndicalist movement. Sonia Hernández tells the story of how Piña and other Mexicanas in the Gulf of Mexico region fought for labor rights both locally and abroad in service to the anarchist ideal of a worldwide community of workers. An international labor broker, Piña never left her native Tamaulipas. Yet she excelled in connecting groups in the United States and Mexico. Her story explains the conditions that led to anarcho-syndicalism's rise as a tool to achieve labor and gender equity. It also reveals how women's ideas and expressions of feminist beliefs informed their experiences as leaders in and members of the labor movement"--